ANALISIS BIAYA VOLUME LABA UNTUK PERENCANAAN LABA PADA PERUSAHAAN ES BATU CAMPLONG DI SAMPANG - Yulianto, Zainal (JURNAL AKUNTANSI DAN INVESTASI, 2018)
Cost-volume-profit analysis is an analysis to find out the relationship between costs, sales volume, profits and product mix to achieve the desired level of profit. The objective to be achieved in this study is to find out about the analysis of profit volume costs in the Ice Cube Camplong Company in profit planning. This type of research uses a type of quantitative descriptive research which is recording data with numbers that are values and can be given an objective picture of the problem under study. So the profit planning that must be targeted by the Es Batu Camplong company is Rp. 107,479 units from the calculation of the profit target of Rp. 328,500.00 from the comparison results from the previous year. So to achieve sales of 25% the company wants in the coming year the company must sell Rp 107,479 units.